CBCT-Aided Microscopic and Ultrasonic Treatment for Upper or Middle Thirds Calcified Root Canals. (25th July 2016) - Yang, Ying-Ming; Guo, Bin; Guo, Li-Yang; Yang, Yan; Hong, Xiao; Pan, Hong-Ying; Zou, Wen-Ling; Hu, Tao
Abstract : Root canal calcification is considered a great challenge during root canal treatment. Although the application of ultrasonic instruments and dental operating microscope (DOM) has advantages, dealing with calcified root canals still suffers a great risk of failure because of limited information about the location, length, and direction of obliteration on periapical radiographs. In this work, a cone-beam computed tomography- (CBCT-) aided method aimed at solving complicated calcified root canals in which conventional approaches could not work was proposed. Thirteen teeth with sixteen calcified canals (12 calcified in the upper third, 4 calcified in the middle third), which cannot be negotiated with conventional methods, were treated with the aid of CBCT. The location of calcification and depth of instrumentation and operating direction were calculated and assessed in three dimensions with ultrasonic instruments under DOM. In all thirteen teeth, canals with upper and middle thirds calcification were treated successfully. Finally, a guideline was proposed to help achieve consistent apical patency in calcified canals.